Illustrated key for the genera of Syrphinae (Diptera, Syrphidae) of occurrence in the South of Brazil - Marinoni, Luciane; Morales, Mírian Nunes; Spaler, Ílven (Biota Neotropica, 2007)
Despite of the richness and abundance of the Syrphidae in the Neotropical Region, the bibliography about the family for this area is relatively scarce. Identification of specimens belonging to this family and, more specifically for those of the subfamily Syrphinae, becomes difficult because of the great variation between the species of a single genus. With the purpose in assisting specialists and non-specialists in identifying the genera of Syrphidae a pictorial key for the subfamilies Eristalinae, Microdontinae and Syrphinae and for the Syrphinae genera occurring in the states of Rio Grande do Sul, Santa Catarina and Paraná, Southern Brazil was prepared. Species of eleven genera have been recorded for the region: Allograpta Osten Sacken, Argentinomyia Lynch Arribálzaga, Leucopodella Hull, Notosyrphus Vockeroth, Ocyptamus Macquart, Platycheirus Lepeletier & Serville, Pseudodoros Becker, Salpingogaster Schiner, Syrphus Fabricius, Toxomerus Macquart and Xanthandrus Verral.